Telaah Artikel: Does Interdependency Affect firm And Industry Profitability? An Empirical Test - Lina Anatan . (Jurnal Manajemen Maranatha, 2011)
Today's business environment characterized is by faster technological development, shorter product life cycle, and more intense global competition. To achieve better performance and sustainable competitive advantage, firms need to optimize interdependent activities to generate and sustain capability heterogeneity among firms. By integrating the competitive and NK model of interdependency, this paper discusses a review concerning the importance of interdependencies among firms productive activities and its effect on firm and industry performance to explain the heterogeneity in capabilities among firms.Keywords: interdependency, firm profitability, industry profitability, sustainable competitive advantage.